At What Cost?: Introduction to the Special Issue "Return on Investment for Academic and Behavioral Assessment and Intervention". Issue 4 (9th December 2020) - Barrett, Courtenay A.; Gadke, Daniel L.; VanDerHeyden, Amanda M.
Abstract: School leaders are tasked with addressing a variety of academic, behavioral, and social–emotional concerns but struggle to do so with limited resources. Because resources are limited, researchers and practitioners need to consider not only what works but also at what cost. Economic evaluations apply specific methods to assess and contextualize the costs and effects of evidence-based practices to help compare interventions and proactively inform resource allocation, but these have rarely been conducted in school psychology. The goals of this special issue are to define economic evaluation methods that could be used in school psychology, to highlight research examining the cost-effectiveness of evidence-based practices, and to examine the costs of translating and scaling evidence-based practices to bridge the research–practice gap. In this introductory article, we describe several methods for conducting economic evaluations, provide empirical demonstrations of these methods, and outline available resources for readers to conduct economic evaluations in the future.